Cross Section Optimization of Offset Parabolic Reflector Antenna for Cosecant-Squared Radiation Pattern - Yucedag, Okan Mert; Makal Yucedag, Senem; Turk, Ahmet Serdar (IEEE, 2013)
This paper presents cross section optimization of offset parabolic reflector antenna structure to obtain cosecant-squared pattern for microwave surveillance radars. Analytical Regularization Method (ARM) and Artificial Neural Network (ANN) are used as a pre-design and optimization tool.
Keywords: Parabolic Reflector Antennas; Cosecant-Squared Pattern; Analytical Regularization Method; Artificial Neural Network; Engineering